Association of scopophobia with online learning fatigue among medical students in Brazil - Mateus Sudário Alencar; Marcos Kubrusly; Claudia Maria Costa de Oliveira; Bianca Oriá Almada de Aquino; Isadora Néri Viana; Pedro Iughetti Morais; Hermano Alexandre Lima Rocha (BMC Medical Education, 2023)
Abstract Background Scopophobia can be described in the medical field as the fear of being watched or stared at. Despite the relevance of scopophobia in remote learning scenarios, which have always existed and have been largely expanded during the pandemic in medical education, studies on this topic are exceedingly rare worldwide. Hence, to fill up this gap, a cross-sectional study of medical students was developed to assess the association of scopophobia with the prevalence of online learning fatigue. Methods A cross-sectional, quantitative, analytical study was carried out in Medical Schools of Brazil. To assess the risk of scopophobia, questions were developed, based on the literature on the topic. The Zoom Exhaustion & Fatigue Scale (ZEF) was used, and the questions have currently been validated for Brazilian Portuguese. Logistic regression models were also used to assess the relationship of scopophobia risk and ZEF scores. Results A total of 283 students from Brazil participated in the study. The median age was 23 years, and 64% of the participants were female. In total, 14.5% were considered to be at high risk for scopophobia. It was found that after adjusting for sex, income and number of residents in the household, scopophobia and the total zoom fatigue score remained associated. For the total score, each additional point on the scale increased the chance of scopophobia by 3%, and for the overall domain, 19% (p-values < 0.05). Conclusions In conclusion, this study shows a relevant prevalence of students with scopophobia, which requires a differentiated approach on the part of teachers. The causes of scopophobia are often specific and have a psychological origin that goes beyond the usual pedagogical management. Therefore, motivation strategies are necessary in a general, as well as an individualized manner, aiming to favor the improvement of the online teaching and learning process.